Relationship between Coach’s Leadership Style and Motivation of Male Athletes - Muhammad Bikri Ash Shiddiq; Ahmad Hamidi; Herman Subarjah (Jurnal Maenpo : Jurnal Pendidikan Jasmani Kesehatan dan Rekreasi, 2023)
Each coach has a distinctive leadership style, and each coach's leadership style has its advantages and disadvantages. Trainers have several leadership behaviors/actions in training. There are several coach-style behaviors, i.e., training/instruction, authoritarian, democracy, social support, and feedback. This study aims to determine whether there is a relationship between the coach's leadership style and male athletes’ motivation. This research method uses a descriptive correlation research design. The samples in this study were active student members of the men's futsal student activity unit of the Indonesian Education University. The data collection technique used a random sampling technique. The instruments used were The Leadership Scale for Sport (LSS) to measure the coach's leadership style and SMS (Social Motivation Scale) to measure male athletes’ motivation. This study was analyzed using parametric statistical analysis with the Pearson correlation test. The results of the data analysis Moreover, the authority leadership style attains a sig value (ρ) of 0.006 <0.05. Hence, H0 is rejected. It is assumed that the coach's leadership style has a significant relationship with the motivation of male athletes of the Futsal Student Activity Unit of the Indonesian Education University. Meanwhile, the sig. value (ρ) of democratic leadership style is 0.031 < 0.05. Thus, H0 is rejected. It means that the democratic coach's leadership style has a significant relationship with the motivation of male athletes of the Futsal Student Activity Unit of the Indonesian Education University. Moreover, the social support leadership style indicates a sig (ρ) value of 0.033 <0.05. Hence, H0 is rejected.indicate that there is a significant relationship between the coach's leadership style and male athletes’ motivation.  Keywords: Coach’s Leadership Style, Motivation